Firebirds - Jeffrey, Gary.; Cappoli, Sara, Illustrator (New York : Gareth Stevens Pub., 2012)
Describes firebirds found in folklore, presents a graphic retelling of "Prince Ivan, the Firebird, and the Wolf," and provides summaries of other tales featuring these mythical creatures.
A blaze of glory -- Prince Ivan, the Firebird, and the Wolf -- Other Firebird tales.
Includes index.
99249
Keywords: Birds -- Juvenile literature; Folklore - Mythical; Graphic novels